Liquefaction characteristics in triaxial tests under various gravity environments – DEM analyses. (April 2023) - Otsubo, Masahide; Chitravel, Sanjei; Kuwano, Reiko; Kyokawa, Hiroyuki; Koseki, Junichi
Abstract: Liquefaction of sands occurs when the effective stress becomes zero during undrained loading, and the state of liquefaction is often considered that individual particles do not transmit contact forces. In shaking table model tests, seepage flows towards the surface occur during liquefaction; this potentially maintains individual particles floated as the gravitational forces can be cancelled out by the upward seepage forces. In laboratory element tests, however, undrained conditions induce no seepage flows during liquefaction. This raises a key question of how the individual particles behave during liquefaction in element tests, and how the macroscopic mechanical response is affected due to gravity. To answer these questions, this contribution conducts a series of triaxial loading simulations using the discrete element method (DEM) considering the effect of gravity on the mechanical response of spherical particle assemblies. The results reveal that the presence of gravity affects both packing properties and liquefaction characteristics. Inter-particle contacts are maintained during liquefaction under non-zero gravity conditions. Although the liquefaction resistance is merely affected due to gravity, the stress–strain relation and stress path are measurably altered. This contribution highlights the importance of considering the potential effect of gravity when laboratory or DEM results on liquefaction phenomena are interpreted.